De profundis - Wilde, Oscar, 1854-1900; Balseiro, María Luisa; Wilde, Oscar, 1854-1900. (Madrid : Ediciones Siruela, 2010)
While imprisoned, Wilde wrote this long letter of recrimination to his lover, Lord Alfred Douglas. It offers fascinating insights into Wilde's life in prison and the background and psychology of a notorious affair.
Online resource; title from ePub title page (Digitalia, viewed March 18, 2016)
Keywords: Wilde, Oscar, -- 1854-1900 -- Correspondence; Authors, Irish -- 19th century -- Correspondence; Prisoners -- England -- Reading -- Correspondence; Douglas, Alfred Bruce, -- 1870-1945 -- Correspondence; Electronic books